Vicente do Rego Monteiro: primitivismo modernista e identidades regionais - Santos, Régis Ferreira Brasilio dos (2011)
Vicente do Rego Monteiro ( born in 1899 Recife, deceased in 1970 Recife), painter and poet from Pernambuco s region by the time of the brazilian modernism appearance, member of a whealthy family whom rulled the suggar commerce and production in the Northeast, he had the opportunity to study at the french accademy in 1911. In 1914, when he returned to Brazil, his sights over the artistic aesthetic had changed, it was different from those academic paitings that was predominant in the brazilian collection and patronage, new themes to be explored, influenced by the french cubism of the great masters Picasso and Léger, involved in the primitivist theme, seeking the art of Marajora and Maracá ceramics as a reference. He was the only one modernist of this time, on an ideal creation moment of a Brazilian National Identification by representing the indian as ther fundamental element in the people s formation and national culture. What most bring us anguish is the fact that besides his importance to the brazilian modernism, and mainly after the Modern Art Week in 1922, in Rio and São Paulo s region, he quit the modernist core, and even being forgotten by the artistic community, he lived his artistic experience in Paris, France, winning poetry awards and solo exposition in town. The purpose of the research is to realize Rego Monteiro s path of artistic sociability, in order to propose possibilities of interpretation of his distant relationship with the modernisn in São Paulo, knowing that before 1930, the comunication with him was through letters and expositions in Paris, and after 1930, they were set appart and Rego isolates himself in Paris until 1956, when he returns to Recife and begins to organize poetry meetings in town. In 1930, Oswald de Andrade invited Rego Monteiro to be part of an anthropophagy group that he had formed with Tarsila do Amaral in 1928 with the launch of the Anthropophagy s magazzine and after, with the Tarsila s work tittled Anthropophagy, 1929. Rego Monteiro alleged that he was the anthropophagy pioneer with the works A caçada, 1923 and by a cartoon tittled Anthopophagy, 1921. In the primitivism studies, we analize sources of plastic works from Vicente Monteiro, analizing his influences and requests, besides his sightseeings over the city, mainly Paris